Pain Management Of Patients With Head And Neck Cancer In Palliative Care: A Literature Review - Isadora Follak de Souza; Guiomar Viana; Letícia Silvestre Gomes Rocha; Raquel Richelieu Lima de Andrade Pontes (Portal de Periódicos da Marinha do Brasil, 2022)
Patients with head and neck cancer (HNC) display limitations and functional impairments. Orofacial pain affects the majority of these patients and may be caused by various factors, both in soft and hard tissues. Patients with advanced stage HNC need to be assisted in a way that promotes quality of life for them and their relatives, as a form of palliative care, especially when the disease is no longer likely to be controlled. Pharmacological analgesia is the backbone of the treatment of cancer pain, but it can also be carried out through non-pharmacological therapies. This study aimed at reviewing the literature and seeking the different pathways to control orofacial pain in patients with HNC in palliative care. Searches in the PubMed and SciELO databases were performed with the words "(pain control) AND (palliative care) AND (head and neck cancer)," aiming to find papers published through the last ten years (2011-2021) and restricting them to clinical trials and randomized clinical trials. We found ten articles in the PubMed database and none in SciELO. After reading their titles and abstracts, we excluded five of them since they did not evaluate patients with HNC nor did they have the analgesic approach as a study objective; therefore, five papers were included in our review. Most studies have shown that analgesia in patients in palliative care affected by malignant head and neck injuries happens with opioids. In this review, we observed a few clinical trials, and further studies must be carried out to seek new ways to reduce symptoms and improve the quality of life of these patients.